2023
DOI: 10.1177/00936502231184318
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory of Credibility Work and Illness: Explication and Application to the Case of Women on Trial in Health Care

Abstract: We make the communicative labor of illness credibility explicit by moving the concept of work into critical interpersonal theory to develop a grounded theory of credibility work. Synthesizing multi-disciplinary literature and drawing on interviews with 36 women in the United States whose health issues have been dismissed by health care providers, friends, and family, we forward a definition of credibility work, six postulates about its nature, and a broad typology of credibility work strategies. We then apply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Medical gaslighting refers to the denial and dismissal of symptoms, invalidation and disregard of patient concerns and wishes, refusal of screening, referral and treatment, gender bias in healthcare, stigmatisation of mental ill health by healthcare professionals, and inadequate care experienced by individuals in medical settings ( 15–17 , 19 , 30–35 ). For example, women may experience being dismissed as lacking credibility when reporting illness symptoms ( 16 , 17 , 26 , 31 , 35 ).…”
Section: Existing Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Medical gaslighting refers to the denial and dismissal of symptoms, invalidation and disregard of patient concerns and wishes, refusal of screening, referral and treatment, gender bias in healthcare, stigmatisation of mental ill health by healthcare professionals, and inadequate care experienced by individuals in medical settings ( 15–17 , 19 , 30–35 ). For example, women may experience being dismissed as lacking credibility when reporting illness symptoms ( 16 , 17 , 26 , 31 , 35 ).…”
Section: Existing Evidencementioning
confidence: 99%
“…A systematic review of the psychological impact of medical gaslighting on women ( 15 ) found the healthcare experiences of women to be overwhelmingly negative and encompassing medical gaslighting, leading to delayed diagnosis, the need for self-advocacy, worsening health conditions and trauma ( 15 ). Experiencing medical gaslighting can lead to women suppressing emotion in clinical settings out of fear of being stigmatised and dismissed ( 35 ), using comprehensive self-management and communication strategies, and self-advocacy in an effort to get needs met and avoid further inequity ( 15 , 34–36 ), feeling that symptoms must need to be severe in order to warrant seeking medical care ( 36 ), and feelings of grief and loss from years spent undiagnosed and untreated ( 37 , 38 ). Due to medical gaslighting, women may also distrust, fear and avoid health services ( 17 , 32 , 34 , 39 ), and under-report their symptoms ( 40 ).…”
Section: Existing Evidencementioning
confidence: 99%
“…Henry’s narrative highlights both unique (and compounding) healthcare dilemmas for patients who are trans, non-binary, and gender diverse (Baker, 2022; Baker et al, 2023; Hudak, 2021). Trans patients and AFAB patients both experience stigma in healthcare interactions that often attribute their symptoms to psychiatric cause, resulting in patients having to employ discursive strategies to receive the care that they need (Baker et al, 2023; Thompson et al, 2023). As a result of these experiences, participants emphasized the importance of learning to trust themselves (and their physiological experiences) again.…”
Section: Findings: Lessons Learned From Narratives Of Autoimmune Diseasementioning
confidence: 99%
“…As a result, emerging adults experiencing the onset of chronic illness symptoms struggle to find stories like theirs, resulting in mental health and identity impacts, including depression, anxiety, and fear for the future (Wilson & Stock, 2019). Due to their age, patients may experience contestation , or disbelief, of their symptoms by healthcare providers (Bontempo, 2022; Hildenbrand et al, 2022) and relational others (e.g., family members, friends; Hintz & Wilson, 2021; Thompson & Duerringer, 2020; Thompson et al, 2023), being told that they are too young to be sick (Gunning, 2022). As a result of contestation and a lack of stories that mirror their own experiences, emerging adults with chronic illness grapple with cognitive dissonance as they compare their former “well” selves to their new “ill” or “abnormal” identities, alongside their “normal” peers and relational others (April et al, 2021; Wilson & Stock, 2019).…”
Section: Introductionmentioning
confidence: 99%